426 The diagnostic value of microRNA signature in endometrial cancer. (13th November 2020) - Donkers, H; Hirschfeld, M; Weiß, D; Erbes, T; Jaeger, M; Pijnenborg, J; Bekkers, R; Galaal, K
Abstract : Background: MiRNAs are noncoding RNAs that regulate gene expression and contribute to the development of cancer. MiRNAs have been shown to be stable in urine, serum and tissue samples. They may be promising biomarkers for non-invasive detection of EC. Methods: A retrospective cohort study of women diagnosed with EC between January 2017 and December 2017 was performed at the Royal Cornwall Hospital. Archived formalin-fixed paraffin-embedded (FFPE) samples were obtained from patients with EC and healthy female subjects. MiRNA was isolated and qPCR was used to detect expression levels of miRNAs. Results: A total of 76 women were included; 36 EC patients, 40 healthy controls. A distinct panel of miR-200a, miR-200b, miR-200c, miR-205 and miR-182 showed AUC of 0.958, sensitivity 92%, specificity 89%, positive predictive value of 89% and negative predictive value of 91% in diagnosing EC. MiR-182 expression levels were significantly related to high-grade endometrioid tumours compared to low grade. Conclusion: We demonstrated high diagnostic accuracy of miRNA for detecting EC. In addition, miRNA contributed to improved distinguishing between high-grade and low-grade endometrioid tumours. Validation of miRNA expression levels in urine will be performed in order to further optimise a non-invasive diagnostic tool.